Chronology of Cuban Reform Policies with Emphasis on Agriculture, 1993-1995 - José Alvarez (EDIS)
The reports included in this series intend to address the increasing level of interest in the Cuban market for food and agricultural products among U.S. firms and to assist them in becoming more familiar with that market. The complete list of documents in this series can be found by conducting a topical search for “Cuba” at http://edis.ifas.ufl.edu, or under "Additional Information" at the end of this document. This is EDIS document FE486, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published July 2004.